If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1x + -1(x + 5) = 1 Reorder the terms: 5x + -1x + -1(5 + x) = 1 5x + -1x + (5 * -1 + x * -1) = 1 5x + -1x + (-5 + -1x) = 1 Reorder the terms: -5 + 5x + -1x + -1x = 1 Combine like terms: 5x + -1x = 4x -5 + 4x + -1x = 1 Combine like terms: 4x + -1x = 3x -5 + 3x = 1 Solving -5 + 3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 3x = 1 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 1 + 5 3x = 1 + 5 Combine like terms: 1 + 5 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 15x^2-25-60= | | 14x-(3x+2)-10=10x-1 | | 25x^2-95x-20= | | 18h^2-42h=0 | | 18x^2+42= | | 12x^2+30= | | x+y+z=4 | | 5x^2=2x+6 | | x-(5x+1)=-3x+(-x+2) | | -x^2+x-20= | | -x^2-7x-18= | | (5-3x)-(-4x+6)=5x+17 | | 2x^2+104=0 | | -x^2-14x+32= | | 5x^2+35x=0 | | 6(x-1)+16(2x+3)=3(2x-7) | | -x^2-11x+30= | | 7x(7x-6)=-18 | | 8(3x-3)=2(12x+7) | | -x^2-9x+18= | | 3x^2-4=-16 | | 8+18n-2=5n+118-3n | | 2x^2+x-8+x=0 | | 3(x+2)+5(x+6)= | | -x^2-20x+51= | | -x^2-8x+7= | | -x^2+12x-32= | | n^2-3n=-5 | | 3m+8m=66 | | -x^2+7x-10= | | 30x-(6-x)+(4-5x)=-(5x+6) | | 9*-17= |